Enhanced External Counterpulsation: A New Option for the Cardiac Patients of Bangladesh - Iqbal, Md Jabed; Siddiqui, Md Mahmudur Rahman; Salehin, Khondaker Syedus; Haque, KMHS Sirajul (Anwer Khan Modern Medical College Journal, 2014)
Abstract not available DOI: http://dx.doi.org/10.3329/akmmcj.v5i1.18840 Anwer Khan Modern Medical College Journal Vol. 5, No. 1: January 2014, Pages 39-41